Compensation Benchmarking Practices in Large U.S. Local Governments: Results of a National Survey. (September 2015) - Thom, Michael; Reilly, Thom
Growing competition over human capital has reiterated the importance of strategic practices to maintaining a high-quality public sector workforce. But how often does the public sector study pay and benefits among competitive peers? This study presents the findings of a national survey of human resource professionals regarding compensation benchmarking practices. Just over half of respondents indicated they conducted a benchmarking study within the last decade. A majority said their jurisdiction only compares compensation with other public employers, with a smaller number including both public and private competitors. Salaries were the most frequent topic of concern; fringe benefits and paid leave time were less often compared. Several jurisdictions conducted benchmarking studies for purposes other than compensation; about one quarter gathered data for purely informational purposes and 9% carried out a study in anticipation of labor negotiations. A series of best practices for benchmarking studies is offered in conclusion.